2012
DOI: 10.2136/sssaj2011.0349
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Dynamics in a Deep Soil-Alluvial Gravel Vadose Zone Following Nitrate Leaching

Abstract: Subsoil denitrification is a potential sink for leached nitrate (NOj") that may otherwise contaminate ground water. A field trial was undertaken to assess the importance of subsoil denitrification and to examine the role of leached NOj" on subsurface nitrous oxide (N2O) (a potent greenhouse gas) dynamics. We monitored NOj", Br", N2O, CO2, and O2 concentrations in alluvial vadose materials to a depth of 7 m over a 32-mo period following the application of N (400 kg ha~^ as NH4NO3) and Br~ to potatoes {Solanum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Overall, N 2 O fluxes were greatest in the soil and subsoil soon after urine application. This is consistent with Thomas et al (2012) who reported that, based on N 2 O flux estimates and NO 3 –N/Br ratios, almost all of the net N 2 O production occurred in the subsoil above gravel material (depth of 1 m). This indicates that in these environments, once N from urine is leached below the subsoil in the gravel matrix, net N 2 O production in the vadose zone is small and that there will be little attenuation of leached NO 3 before it is transported to groundwater.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, N 2 O fluxes were greatest in the soil and subsoil soon after urine application. This is consistent with Thomas et al (2012) who reported that, based on N 2 O flux estimates and NO 3 –N/Br ratios, almost all of the net N 2 O production occurred in the subsoil above gravel material (depth of 1 m). This indicates that in these environments, once N from urine is leached below the subsoil in the gravel matrix, net N 2 O production in the vadose zone is small and that there will be little attenuation of leached NO 3 before it is transported to groundwater.…”
Section: Discussionsupporting
confidence: 92%
“…The declining NO 3 –N/Br ratios in the soil zone (0.6 and 1.0 m) during the winter spring period (July 2007–October 2007) indicated that some denitrification may have occurred (Fig. 3 and Table 1) as reported in similar conditions by Thomas et al (2012), though the changing ratios may have been a result of differential N uptake in the root zone followed by a leached pulse with different ratios. Within the underlying alluvial gravel vadose zone, there was no evidence that NO 3 –N to Br ratios were changing due to denitrification.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In other cases, much of the N 2 O trapped at depth may be removed as melting water infiltrates the subsurface and recharges the groundwater. This N 2 O loss mechanism is poorly studied and rarely quantified (Outram and Hiscock 2012;Thomas et al 2012).…”
Section: Freeze á Thaw Emissions: Physical Releasementioning
confidence: 99%